The contribution of monetary rewards, social rewards and promotions on worker performance(small-business of textile and its products) - Firman Fauzi; Inka May Dorry (Manajemen dan Bisnis, 2022)
This study aims to analyze the effect of financial rewards, interpersonal rewards and promotions on employee performance. The population in this study were employees in the textile industry company. The sample used was 30 respondents. Respondent sampling method used in this research is saturated sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method uses statistical analysis in the form of multiple linear regression tests. The analysis tool uses the SPSS version 26 application. The results of this study indicate that the variable financial rewards, interpersonal rewards and promotions have a positive and significant effect on employee performance variables.